2000
DOI: 10.1161/01.cir.102.19.2347
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Raises HDL Cholesterol Levels by Increasing the Transport Rate of Apolipoproteins A-I and A-II

Abstract: Alcohol intake increases HDL-C in a dose-dependent fashion, associated with and possibly caused by an increase in the TR of HDL apolipoproteins apoA-I and -II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(121 citation statements)
references
References 29 publications
9
109
2
1
Order By: Relevance
“…A consistent body of evidence suggests a positive relation between moderate alcohol consumption and HDL cholesterol (De Oliveira E Silva et al, 2000;Baer et al, 2002). In a metaanalysis conducted by Rimm et al (1999), 30 g alcohol/day was associated with an increase in HDL cholesterol concentrations of 0.10 mmol/l (3.99 mg/dl) compared to nondrinkers, which is lower than observed in our study.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…A consistent body of evidence suggests a positive relation between moderate alcohol consumption and HDL cholesterol (De Oliveira E Silva et al, 2000;Baer et al, 2002). In a metaanalysis conducted by Rimm et al (1999), 30 g alcohol/day was associated with an increase in HDL cholesterol concentrations of 0.10 mmol/l (3.99 mg/dl) compared to nondrinkers, which is lower than observed in our study.…”
Section: Discussioncontrasting
confidence: 82%
“…Although some studies showed an effect between alcohol consumption and total glyceride level Baer et al, 2002), many did not (Rumpler et al, 1999;De Oliveira E Silva et al, 2000;Nanchahal et al, 2000). The conflicting results may be due to uncontrolled confounding, such as pre-existing hypertriglyceridaemia, obesity, and length of fasting prior to venipuncture.…”
Section: Alcohol and Risk Factors Of Cardiovascular Disease M Burger mentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between these two parameters is substantially linear, going from nondrinkers to heavy alcohol drinkers (more than six drinks per day) (Lacko et al, 2000). Apo A1 levels, the major HDL apolipoproteins, also respond favourably to a daily intake of alcohol (De Oliveira e Silva et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that alcohol consumption can raise HDL-C levels by increasing the transport of its apolipoproteins (De Oliveira et al 2000). Does the ALDH2 *504Lys allele also affect lipid levels in the body?…”
Section: Traditional Cardiovascular Risk Factorsmentioning
confidence: 99%